Strategic antecedents of innovation: Variance between small and large firms. (2nd January 2021) - Davis, Phillip E.; Bendickson, Joshua S.
ABSTRACT: Our study explores differences in enhancing innovation based on firm size. Framed through the resource-based view, we theorize and test antecedents of innovation including dynamic capabilities, strategic planning, and organizational structure. We operationalize firm size based on number of employees and also include firm revenues as an alternative proxy. We find that dynamic capabilities partially support innovation in both small and large firms. Secondly, we find strategic planning is valuable for small firm innovation and that organizational structure has a positive effect on large firm innovation. Results are largely consistent when comparing number of employees to revenues.